Visual Elements In The Arabic Lectural Book Ministery Of Religion: School Perspectives - Fadilah, Nurul; Sukari, Afaf Binti; Arisy, Zyk Farhad (Journal of Arabic Language Studies and Teaching, 2024)
Since 1968, Resources for Arabic education and learning have continued to advance, thanks to recent technological advancements. Junior high school Arabic textbooks have also been updated based on several factors, including correcting numerous errors and material organization to optimize use and circulation. Researchers discovered that this study, which revealed the visual aspects of the book released by Kemenag in 2020 from the perspectives of Sudarma and Erin M. McTigue, was conducted using exploratory qualitative research and descriptive analysis methodologies. Tables and 180 cartoon pictures or photos comprise most of the book's visual aspects; the remaining elements are design elements, including circles, blunt boxes, and other shapes. Readers may find it challenging to see some layout conditions because they are still random.